The Effect of Employee Work Attitudes on Employee’s Job Performance at Miyana Hotel Medan - Jimmy Kelana; Tina Linda; Devia Febrina (Jurnal Kolaboratif Sains, 2024)
Work Attitude of an employee at work relates to his/her job performance. Job performance of an employee is concerned with two aspects. First, employee should perform his/her job in such a manner that it leads to achievement of desirable ends. Second, he/she should use organizational resources efficiently by avoiding or minimizing the waste in performing the job activities. These attitudes reflect a particular person’s likes and dislikes towards other people, objects, events and activities in that person’s surrounding environment. Some of the strong attitudes are likely to affect person’s behavior and this makes the enthusiasm to study and know about attitudes. Work attitude of an employee at work relates to his/her job performance. Miyana Hotel has problem which the performance of the employees which the employees do not do their jobs with good results in terms of quality which can be seen from customer’s complaints and whenever there is supervisor, employees don’t perform their job. The employees tend to have conflict among them. According to the GM of the hotel, these conditions are associated with the employees being not satisfied with their job because they don’t have opportunity for higher position. The population that is used in the research is the total employees who are active working in Miyana Hotel Medan that are 93 people. The sampling technique is called as census sampling. Census sampling method is method which takes all the population as the sample. In analyzing questionnaires, the writer used validity test and reliability test, to analyze the data, use statistics, correlation test, determination test, linear regression, and hypothesis test. The correlation test shows work attitudes have a positive and significantly strong effect on employees’ job performance at Miyana Hotel Medan. zcount > ztable (8.10 > 1.96), This means the Null hypothesis (Ho) is rejected and the alternative (Ha) is accepted. Work Attitudes have effect on employees’ job performance at Miyana Hotel Medan.